3D simulation and parametric optimization of a solar air heater with a novel staggered cuboid baffles. (1st September 2021) - Parsa, H.; Saffar-Avval, M.; Hajmohammadi, M.R.
Highlights: 3D numerical study of novel staggered cuboid baffles placed on the absorber plate of SAH is investigated. Parametric optimization is conducted for baffle geometries by applying Taguchi experimental design method. The proposed baffles have simple shapes and are easy and economical to manufacture. Relative baffle height and pitch have the most impact on both η and THPP . The Nu of baffled SAH cases was greater than the smooth duct up to 4.34 times and the THPP of the optimum baffled SAH reached 3.43 . Abstract: Thermal performance enhancement of solar air heaters is critical for efficient utilization of energy. In the present work, a numerical study and parametric optimization of turbulent convective heat transfer in a solar air heater duct with novel staggered cuboid baffles placed on the absorber plate are investigated. The heat transfer and pressure loss characteristics are analyzed, and an optimization procedure based on the Taguchi experimental design method is used to obtain the baffle's optimum geometry and arrangement. The numerical results reveal that the proposed optimum design performs better than the existing ones. It is also indicated that the relative baffle height ( c/H ) and relative baffle pitch ( s/H ) are the most influential parameters on the efficiency and thermo-hydraulic performance factor. Also, the thermo-hydraulic performance factor of the optimum baffled solar air heater is 3.43, 2.80 and 2.38 at Reynolds numbers 5080, 7620 and 10160, respectively. Depending on the Reynolds number, the thermo-hydraulic performance factor of the proposed baffled is up to 17.5% better compared with the performance of the best design reported in the literature. Graphical abstract: Image, graphical abstract